Ligand Exchange Strategy for Tuning of Helicity Inversion Speeds of Dynamic Helical Tri(saloph) Metallocryptands. Issue 12 (25th January 2019) - Sakata, Yoko; Chiba, Shunsuke; Miyashita, Masato; Nabeshima, Tatsuya; Akine, Shigehisa
Abstract: We developed a new strategy, ligand exchange strategy, for tuning the response speeds of helicity inversion of a metal‐containing helical structure. This is based on the exchange of the two axial amine ligands of the octahedral Co 3+ centers in the metallocryptands [LCo3 X6 ] (X=axial amine ligand). The response speeds of the helicity induction were controlled by using different combinations of achiral and chiral amines as the starting and entering ligands, respectively. The response speeds of the helicity inversion from P to M were also tuned by using different combinations of chiral amines. Abstract : The response speeds of helicity inversion were efficiently controlled by the ligand exchange strategy using a metal‐containing helical structure. The ligand exchange between different kinds of achiral and chiral amines as the starting and entering ligands resulted in a variation of the response speeds both in the helicity induction and helicity inversion.